Over-the-Air Computing under Adaptive Channel State Estimation - Evgenidis, Nikos G.; Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (International Conference on Wireless and Mobile Computing, Networking and Communications, 2022)
Over-the-air Computation (AirComp) has attracted significant attention as an efficient way of data fusion by inte-grating uncoded communication transmissions with computation thanks to the superposition offered by the multiple access channels. However, proper pre-processing and post-processing is required to neutralize the wireless channel effect, in order for AirComp to function successfully. Since, internet-of-things (IoT) type of devices with limited capabilities are the target de-mographic of AirComp, having perfect channel state information (CSI) available is not always a practical assumption. In this work, we examine the effect of imperfect CSI on the AirComp system and we design a general optimization framework that takes into account both magnitude and phase errors in CSI. On top of that, a pilot retransmission policy is designed that offers a trade-off between cost of retransmissions and gain in the accuracy of the computations. Simulation results show the deterioration caused by the imperfect CSI and also the value of the proposed policy under various system conditions.
Created from Fastlane, Scopus look-up
Keywords: AirComp; imperfect CSI; MSE minimization; optimization framework; over-the-air computing